Development of Expert System Program for Pre-diagnosis of Important Swine Gastrointestinal Diseases in Thailand - Maneelertu-dom, Farpailin; Chaunchom, Sujate; Sookmanee, Neramit; Thaipakdee, Supaporn (Agriculture and Natural Resources, 2012)
This paper discusses the creation of a computer program named “Development of Expert System Program for Pre-diagnosis of Important Swine Gastrointestinal Diseases in Thailand”. The system developer designed the Program for ease of use with a help menu to assist users. The Program has been designed using the programs Microsoft Visual Basic, Microsoft Access and Crystal Report. The references on the gastrointestinal system in swine used in the Program were acquired from those in The Guidance Book for Diagnosis, Treatment and Control Swine Disease by Urairong (1987). The system developer not only had the Program tested among target samples of swine farmers but also conducted a users’ satisfaction survey on various aspects of the Program, as a tool for swine farmers in decision making on the proper initial treatment for their swine in the absence of a veterinarian. The expert system contains 17 diseases, 12 symptom groups, 38 symptoms and 31 gross or macroscopic fecal characters. Users can record information on their swine farming and on the history of their diagnosis and treatments. Notably, the Program can help swine farmers make their initial diagnosis but some swine diseases must later be conﬁ rmed by a scientiﬁ c laboratory. With regard to the satisfaction survey among the users based on a sample involving 500–2,000 sows located in Nakhon Pathom and in Ratchaburi provinces, Thailand, there was high satisfaction expressed with each reviewed aspect—overall satisfaction with the Program design (mean = 3.83), ease of use of diagnose diseases (3.90), suitability and accuracy of the diagnostic information (both 3.77) and understanding the handbook (3.87) and the users’ overall satisfaction with the Program (3.83).